Kekhawatiran Privasi pada Kesuksesan Adopsi FinTech menggunakan Model DeLone dan McLean - Dhiona Ayu Nani; Lia Febria Lina (Faculty of Economics and Business Universitas Jenderal Soedirman, 2020)
ABSTRACT Industry 4.0 has produced many changes in all fields of industry, one of which is FinTech as an innovation in the financial sector. This study aims to fill the gaps of various previous studies by testing the DeLone and McLean Models. As well as testing how the role of privacy concerns can reduce perceptions of information quality in intentions to use FinTech. The object of this research is SMEs in Indonesia. The results of this study indicate that perceptions about the quality of information and services have a positive and significant effect on intention to use FinTech. The factor of privacy concern as a moderating variable has an important role in influencing the intention to adopt technology, so someone who has high concerns can reduce the intention to use online loans. OJK as the owner of the highest authority in the field of finance and banking, is expected to be able to guarantee the safety of online loans, in order to reduce the concerns of MSME owners regarding data that might be misused if using online loans.